Controlling factors for dawsonite diagenesis: a case study of the Binnan Region in Dongying Sag, Bohai Bay Basin, China. Issue 2 (17th February 2016) - Li, F-L.; Li, W-S.
ABSTRACT: Authigenic minerals and the diagenetic sequence of the dawsonite-bearing sandstones from the Binnan Region of the Dongying Sag, Bohai Bay Basin, China were studied to understand the formation of dawsonite, as a possible mechanism for mineral trapping of CO2 in carbon capture and storage (CCS) programmes. Authigenic minerals include quartz overgrowth, dawsonite (5–15 vol%), calcite, ferrocalcite and ankerite. The major rock types are medium- to fine-grained arkose, feldspathic litharenite and lithic arkose. Quantitative analysis suggests that the burial depth and feldspar content are the two dominant controlling factors of the growth of dawsonite. The dawsonite content increases initially before decreasing with burial depth, with the peak dawsonite content occurring at approximately 1500 m depth. This trend is probably due to increases in temperature and pCO2 with the burial depth and contributes to the formation of dawsonite. However, the pCO2 content and stability of dawsonite decrease with increasing distance from the centre of the gas reservoir. When the formation temperature exceeds the upper limit of the preservation temperature of dawsonite, the dawsonite is suppressed, while the dissolution of dawsonite is promoted. Overall, the dawsonite content exhibits a positive correlation with the feldspar content. The dissolution of feldspar makes both Na + and Al 3+ available and creates the accommodation space necessary for dawsonite growth. In addition, feldspar dissolution also neutralises the acidity of the thermal fluid present, which again facilitates the growth and preservation of the dawsonite.